Biomass production, carbon sequestration potential and productivity of different peanut (Arachis hypogaea)-based cropping systems and their effect on soil carbon dynamics - JAIN, N K; MEENA, H N; YADAV, R S; JAT, R S (The Indian Journal of Agricultural Sciences, 2018)
A field experiment was conducted during 2011-12 and 2012-13 at Junagadh (Gujarat) with fourteen treatment combinations comprising cropping systems, tillage, crop residues incorporation and green manuring with three replications. Results revealed that maximum biomass production (30.05 t/ha) and carbon sequestration potential (12.63 t/ha) were recorded under peanut (Arachis hypogaea L.)+pigeonpea [Cajanus cajan (L.) Millsp.]-Sesbania cropping system. On the other hand, maximum peanut-pod equivalent yield (3.64 t/ha) was obtained under peanutwheat (ZT)-Sesbania which was significantly higher by 102.2 per cent compared to sole peanut. The inorganic soil carbon was significantly altered in peanut-based cropping systems whereas soil organic carbon (SOC) was found non-significant both in plough and sub-soil layers. The highest labile soil carbon was recorded under peanut-wheat (ZT)-Sesbania cropping system (0.77 g/kg) under plough soil layer. On the other hand, the highest non-labile soil carbon was found in peanut-wheat (ZT) (7.07 to 8.03 g/kg) with and without plant residues incorporation at both soil depths (i.e. plough and sub-soil layers). The inorganic carbon increased appreciably (3 to 57%) with increase in soil depth. In contrary, values of organic, labile and non-labile soil carbons, showed declining trend with the increase in soil depth under these cropping systems. In general, the highest values of all soil carbon fractions were observed in peanut-wheat (ZT) at all the soil depths except 15-30 cm for inorganic carbon. The highest MBC (441 mg/kg), SOC stock (17.3 t/ha) and CMI (188.8) were registered under peanut-wheat (ZT)-Sesbania while MQ was higher in peanut-wheat (CT) (4.90%).